Industrial Structure and Capital Flows - Jin, Keyu (American Economic Review, 2012)
This paper provides a new theory of international capital flows. In a framework that integrates factor-proportions-based trade and financial capital flows, a novel force emerges: capital tends to flow toward countries that become more specialized in capital-intensive industries. This “composition” effect competes with the standard force that channels capital toward the location where it is scarcer. If the composition effect dominates, capital flows away from the country hit by a positive labor force/productivity shock—a flow “reversal.'' Extended to a quantitative framework, the model generates sizable current account imbalances between developing and developed countries broadly consistent with the data. (JEL F14, F21, F32, F41, L16, O19)